A new genus and species of deep-sea wood-boring shipworm (Bivalvia: Teredinidae) Nivanteredo coronata n. sp. from the Southwest Pacific. Issue 8 (14th September 2018) - Velásquez, Marcel; Shipway, J. Reuben
ABSTRACT: Nivanteredo gen. nov. coronata sp., a new genus and species from the wood-boring bivalve family Teredinidae, is described. Multiple specimens were collected off the coasts of Vanuatu, the Solomon Islands and Papua New Guinea, between October 2004 and August 2014, from both sunken driftwood and deployed wooden panels at depths of 240–773 m. A combination of features identify these specimens as both a new genus and species, including: unique calcareous pallets distinct from those of all other previous described genera, featuring a central stalk that runs almost the entire length of the blade and a disk shaped periostracal awning adorning the proximal pallet; an elongated mantle collar, extending from the base of the siphons to the mid-stalk of the pallets; a distinctive and elongated auricle on the dorsal shell valve; a complex caecum (wood-storing organ) featuring a highly coiled typhlosole, which ranks as one of the largest relative to total body length among the family. Larval settlement on wooden panels placed at 441 m represents the deepest distribution range of any known teredinid, which were previously thought to be restricted to waters above 200 m. The discovery of Nivanteredo coronata, recruiting at depths more than twice those previously recorded for tereinids, raises the possibility of a hidden diversity in other deep-sea locations and suggests that previous sampling, which has largely been limited to shallow coastal waters, has skewed our understanding on the biogeography and distribution of this family. To aid future identification and systematics of this complex family, we produced a revised and updated appendix of both internal and external characters across the Teredinidae, including the new genus Nivanteredo . http://zoobank.org/urn:lsid:zoobank.org:pub:24216C86-CCB0-4B27-8FE2-89338969E32E GRAPHICAL ABSTRACT: